SILVER NANOPARTICICLES FROM ENTOMOPATHOGENIC FUNGI AGAINST THE SPINY BOLLWORM, EARIAS INSULANA IN MAIZE CROP - Mohamed Abdel-Raheem; Ismail A. Ismail; Ragab S. Abdel-Rahman (Mesopotamia Journal of Agriculture)
The spiny bollworm, (SBW) Earias insulana (Lepidoptera: Noctuidae) is considered one of the most important corn pests in the world. It causes severe damage, resulting in a great loss in both quality and quantity of Maize yield. The study aimed to evaluate the virulence of fungal spores and silver nanoparticles (AgNPs) from entomopathogenic fungi (EPF) on E. insulana under laboratory conditions. Concentrations of the fungal spores and the silver nanoparticles were prepared from Metarhizium anisopliae, Beauveria bassiana, and Verticillium lecanii. Metarhizium anisopliae isolated from larvae and adults of the beet moth and Beauveria bassiana isolated from the beet beetle. The compound was used Bio Catch (V. lecanii). The concentration of EPF used was (1x106 spores/ ml). Hundred larvae and pupae were used for each treatment, divided into 5 groups, and kept at 24±2 ºC and 65±5 % R.H. Silver nanoparticles were synthesized. The nano-particle solution was sprinkled over the filter paper and incubated at 24±2ºC for 3 days. The mortality rate was recorded 2 days after the treatment and mortality percentage was calculated. One-way ANOVA was used to compare the effects of the experimental and control treatments. The results showed that the three EPF achieved (47–70%) mortality rates within 6 days in larvae stage. B. bassiana and M. anisopliae were the most effective ones than V. lecanii. Spores of B. bassiana increased larvae mortality. The larvae mortality rate was (70 %) higher than the control. Pupae mortality rate was 65 % achieved in 6 days when treated with B. bassiana, (60 %) with M. anisopliae and (50%) with V. lecanii. B. bassiana was more effective on E. insulana than M. anisopliae and V. lecanii. The Ag NPs synthesized through applications of spore suspension and biosynthesized silver nanoparticles showed efficacy against E. insulana, different stages.